2016
DOI: 10.3945/jn.116.232223
|View full text |Cite
|
Sign up to set email alerts
|

Minerals and Trace Elements in Human Breast Milk Are Associated with Guatemalan Infant Anthropometric Outcomes within the First 6 Months

Abstract: Breast milk may be inadequate in selected minerals and trace elements where higher estimated intakes were associated with greater infant growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 35 publications
1
47
3
3
Order By: Relevance
“…We selected 3 weeks since this is approximately the age when breast milk Mn concentrations stabilize after declining from initially relatively high levels (Table 1) [21,25,27,35,44,45]. We selected 4.25 months since this is the oldest age at which an infant is likely to be exclusively fed with breast milk or infant formulas [46,47] and is within the recommended ages for products labeled age stage 1 (0-6 months) from the French market or "infant formula" from the US market (0-12 months).…”
Section: Selecting Ages For Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected 3 weeks since this is approximately the age when breast milk Mn concentrations stabilize after declining from initially relatively high levels (Table 1) [21,25,27,35,44,45]. We selected 4.25 months since this is the oldest age at which an infant is likely to be exclusively fed with breast milk or infant formulas [46,47] and is within the recommended ages for products labeled age stage 1 (0-6 months) from the French market or "infant formula" from the US market (0-12 months).…”
Section: Selecting Ages For Comparisonmentioning
confidence: 99%
“…Longitudinal studies have found that the Mn concentration of breast milk is generally highest in colostrum, declines over the first few days or weeks, then remains relatively stable in mature milk (Table 1) [21,24,25,27,35,39,40,44,45,60]. Table 2.…”
Section: Manganese Concentrations In Breast Milkmentioning
confidence: 99%
“…ile Li ve ark.nın çalışmalarına benzer şe-kilde, çalışmamızda, laktasyon ilerledikçe anne sütü Zn düzeylerinde her iki grupta anlamlı azalma olduğu da düşünülürse bölgemizde anne sütü alan bebeklerde Zn desteği ihtiyacının daha geniş çalış-malarla araştırılması gerekmektedir. 17,26 Anne sütü Cu düzeyleri ise çalışmamızda preterm bebeklerde ortalama 0,533±0,158 mg/L saptanır iken, term bebeklerde 0,562±0,160 mg/L bulunmuştur. Dünya genelinde farklı sonuçlar mevcut olup, anne sütü Cu düzeyi Kayseri'de 0,05 (0,01-0,09) mg/L; Adana'da ise term bebeklerde 0.28±0,08 mg/L, pretermlerde 0,28±0,03 mg/L bulunmuş, Björklund ve ark.nın çalışmasında ise 0,471±0,07 mg/L saptanmıştır.…”
Section: Discussionunclassified
“…These findings were similar to a study of 120 healthy mothers in four regions in China that reported manganese concentrations in term breast milk in the first month postpartum (0.5 -2.1 µg/L) (230). In direct contrast however, Li et al reported concentrations of manganese in term breast milk that ranged from 9.33 to11.53 µg/L during the first two months postpartum, which then decreased to a mean value of 7.69 µg/L during 4-6 months postpartum (231). These values were more than five-fold higher than the findings of the present study.…”
Section: Discussionmentioning
confidence: 98%
“…concentrations of manganese in term breast milk that ranged from 9.33 to11.53 µg/L (2 months), which then decreased to a mean value of 7.69 µg/L (4-6 months) over postpartum period (231). Manganese has been characterised in human milk as follows: 67% bound to lactoferrin, 11% to casein, 18% attached with fat globule membrane, and the remaining proportion present in low molecular weight form (225), and thus bioavailability is higher in human milk than formula milk (232).…”
Section: Manganese In Human Milkmentioning
confidence: 98%